ANALYSIS OF VARIOUS TECHNIQUES USED FOR PERIODONTAL FLAP SURGERY - AN INSTITUTIONAL BASED RETROSPECTIVE STUDY - Binti Abd Rahman, Fahmida; Ganesh S, Balaji; T.N., Uma Maheshwari (International Journal of Psychosocial Rehabilitation, 2020)
Periodontal therapy is directed at disease prevention, slowing or arresting disease progression, regenerating lost periodontium, and maintaining achieved therapeutic objectives. One of the most common surgical procedures done in the oral cavity is the periodontal flap surgery. Reconstructive periodontal procedures may improve tooth survival while minimizing the progression of periodontitis and re-intervention needs provide long term outcome stability. The study aims at analyzing the various flap techniques used in periodontal flap surgery among patients attending a private dental institution. We reviewed 42,110 patient records and it was found out that 722 patients matched the inclusion criteria. Chi square test was done for statistical analysis and the association between various flap techniques and periodontal diseases was found to be statistically significant with p value<0.05. Within the limit of our study, it can be concluded that the Kirkland flap technique was most commonly followed by surgeons for periodontal flap surgery. Males had higher prevalence for undergoing periodontal flap surgery than females. Generalized chronic periodontitis patients aged less than 45 years old had mostly undergone periodontal flap surgery.